Question Number 177542 by peter frank last updated on 06/Oct/22
Answered by Frix last updated on 07/Oct/22
$$\mathrm{9}°={x} \\ $$$$\mathrm{27}°=\mathrm{3}{x} \\ $$$$\mathrm{tan}\:\left(\mathrm{90}°−{x}\right)\:=\frac{\mathrm{1}}{\mathrm{tan}\:{x}} \\ $$$$\mathrm{81}°=\mathrm{90}°−\mathrm{9}° \\ $$$$\mathrm{63}°=\mathrm{90}°−\mathrm{27}° \\ $$$$\mathrm{tan}\:{x}\:=\frac{\mathrm{sin}\:{x}}{\mathrm{cos}\:{x}} \\ $$$$\mathrm{tan}\:\mathrm{3}{x}\:=\frac{\mathrm{tan}^{\mathrm{3}} \:{x}\:−\mathrm{3tan}\:{x}}{\mathrm{3tan}^{\mathrm{2}} \:{x}\:−\mathrm{1}}=\frac{\left(\mathrm{sin}^{\mathrm{2}} \:{x}\:−\mathrm{3cos}^{\mathrm{2}} \:{x}\right)\mathrm{sin}\:{x}}{\left(\mathrm{3sin}^{\mathrm{2}} \:{x}\:−\mathrm{cos}^{\mathrm{2}} \:{x}\right)\mathrm{cos}\:{x}} \\ $$$$\mathrm{tan}\:{x}\:+\frac{\mathrm{1}}{\mathrm{tan}\:{x}}−\left(\mathrm{tan}\:\mathrm{3}{x}\:+\frac{\mathrm{1}}{\mathrm{tan}\:\mathrm{3}{x}}\right)= \\ $$$$=\frac{\mathrm{2}\left(\mathrm{sin}^{\mathrm{2}} \:{x}\:−\mathrm{2cos}\:{x}\:\mathrm{sin}\:{x}\:−\mathrm{cos}^{\mathrm{2}} \:{x}\right)\left(\mathrm{sin}^{\mathrm{2}} \:{x}\:+\mathrm{2cos}\:{x}\:\mathrm{sin}\:{x}\:−\mathrm{cos}^{\mathrm{2}} \:{x}\right)}{\mathrm{cos}\:{x}\:\mathrm{sin}\:{x}\:\left(\mathrm{sin}^{\mathrm{2}} \:{x}\:−\mathrm{3cos}^{\mathrm{2}} \:{x}\right)\left(\mathrm{3sin}^{\mathrm{2}} \:{x}\:−\mathrm{cos}^{\mathrm{2}} \:{x}\right)} \\ $$$$\mathrm{sin}^{\mathrm{2}} \:{x}\:=\frac{\mathrm{1}−\mathrm{cos}\:\mathrm{2}{x}}{\mathrm{2}} \\ $$$$\mathrm{cos}^{\mathrm{2}} \:{x}\:=\frac{\mathrm{1}+\mathrm{cos}\:\mathrm{2}{x}}{\mathrm{2}} \\ $$$$\mathrm{cos}\:{x}\:\mathrm{sin}\:{x}\:=\frac{\mathrm{sin}\:\mathrm{2}{x}}{\mathrm{2}} \\ $$$$\mathrm{now}\:\mathrm{we}\:\mathrm{have} \\ $$$$\frac{\mathrm{4}\left(\mathrm{cos}^{\mathrm{2}} \:\mathrm{2}{x}\:−\mathrm{sin}^{\mathrm{2}} \:\mathrm{2}{x}\right)}{\left(\mathrm{4cos}^{\mathrm{2}} \:\mathrm{2}{x}\:−\mathrm{1}\right)\mathrm{sin}\:\mathrm{2}{x}}=\frac{\mathrm{4}\left(\mathrm{2cos}^{\mathrm{2}} \:\mathrm{2}{x}\:−\mathrm{1}\right)}{\left(\mathrm{4cos}^{\mathrm{2}} \:\mathrm{2}{x}−\mathrm{1}\right)\mathrm{sin}\:\mathrm{2}{x}}= \\ $$$$=\frac{\mathrm{4cos}\:\mathrm{4}{x}}{\mathrm{sin}\:\mathrm{6}{x}} \\ $$$$\mathrm{but}\:{x}=\mathrm{9}° \\ $$$$\frac{\mathrm{4cos}\:\mathrm{36}°}{\mathrm{sin}\:\mathrm{54}°} \\ $$$$\mathrm{but}\:\mathrm{sin}\:\left(\mathrm{90}°−{x}\right)=\mathrm{cos}\:{x} \\ $$$$\frac{\mathrm{4cos}\:\mathrm{36}°}{\mathrm{cos}\:\mathrm{36}°}=\mathrm{4} \\ $$
Commented by peter frank last updated on 07/Oct/22
$$\mathrm{thank}\:\mathrm{you} \\ $$
Answered by Ar Brandon last updated on 07/Oct/22
$${T}=\mathrm{tan9}°−\mathrm{tan27}°−\mathrm{tan63}°+\mathrm{tan81}° \\ $$$$\:\:\:=\left(\mathrm{tan9}°+\frac{\mathrm{1}}{\mathrm{tan9}°}\right)−\left(\mathrm{tan27}°+\frac{\mathrm{1}}{\mathrm{tan27}°}\right) \\ $$$$\:\:\:=\frac{\mathrm{tan}^{\mathrm{2}} \mathrm{9}°+\mathrm{1}}{\mathrm{tan9}°}−\frac{\mathrm{tan}^{\mathrm{2}} \mathrm{27}°+\mathrm{1}}{\mathrm{tan27}°}=\frac{\mathrm{sec}^{\mathrm{2}} \mathrm{9}°}{\mathrm{tan9}°}−\frac{\mathrm{sec}^{\mathrm{2}} \mathrm{27}°}{\mathrm{tan27}°} \\ $$$$\:\:\:=\frac{\mathrm{1}}{\mathrm{sin9}°\mathrm{cos9}°}−\frac{\mathrm{1}}{\mathrm{sin27}°\mathrm{cos27}°}=\frac{\mathrm{2}}{\mathrm{sin18}°}−\frac{\mathrm{2}}{\mathrm{sin54}°} \\ $$$$\:\:\:=\frac{\mathrm{2}\left(\mathrm{sin54}°−\mathrm{sin18}°\right)}{\mathrm{sin18}°\mathrm{sin54}°}=\frac{\mathrm{4sin18}°\mathrm{cos36}°}{\mathrm{sin18}°\mathrm{sin54}°} \\ $$$$\:\:\:=\frac{\mathrm{4sin18}°\mathrm{sin54}°}{\mathrm{sin18}°\mathrm{sin54}°}=\mathrm{4} \\ $$
Commented by peter frank last updated on 07/Oct/22
$$\mathrm{thank}\:\mathrm{you} \\ $$
Answered by Frix last updated on 07/Oct/22
$$\mathrm{or}: \\ $$$$\mathrm{tan}\:\mathrm{9}°\:+\mathrm{tan}\:\mathrm{81}°\:=\mathrm{tan}\:\mathrm{9}°\:+\frac{\mathrm{1}}{\mathrm{tan}\:\mathrm{9}°}= \\ $$$$\left[\frac{\mathrm{s}}{\mathrm{c}}+\frac{\mathrm{c}}{\mathrm{s}}=\frac{\mathrm{s}^{\mathrm{2}} +\mathrm{c}^{\mathrm{2}} }{\mathrm{cs}}=\frac{\mathrm{1}}{\mathrm{cs}}\right] \\ $$$$=\frac{\mathrm{1}}{\mathrm{cos}\:\mathrm{9}°\:\mathrm{sin}\:\mathrm{9}°} \\ $$$$\mathrm{similar} \\ $$$$−\left(\mathrm{tan}\:\mathrm{27}°\:+\mathrm{tan}\:\mathrm{63}°\right)=−\frac{\mathrm{2}}{\mathrm{sin}\:\mathrm{54}°}=−\frac{\mathrm{2}}{\mathrm{sin}\:\left(\mathrm{6}×\mathrm{9}°\right)}= \\ $$$$\left[\mathrm{sin}\:\mathrm{6}{x}\:=\mathrm{2cos}\:{x}\:\mathrm{sin}\:{x}\:\left(\mathrm{3}−\mathrm{16cos}^{\mathrm{2}} \:{x}\:\mathrm{sin}^{\mathrm{2}} \:{x}\right)\right. \\ $$$$=\frac{\mathrm{1}}{\mathrm{cos}\:\mathrm{9}°\:\mathrm{sin}\:\mathrm{9}°\:\left(\mathrm{16cos}^{\mathrm{2}} \:\mathrm{9}°\:\mathrm{sin}^{\mathrm{2}} \:\mathrm{9}°\:−\mathrm{3}\right)} \\ $$$$\frac{\mathrm{1}}{\mathrm{cos}\:\mathrm{9}°\:\mathrm{sin}\:\mathrm{9}°}+\frac{\mathrm{1}}{\mathrm{cos}\:\mathrm{9}°\:\mathrm{sin}\:\mathrm{9}°\:\left(\mathrm{16cos}^{\mathrm{2}} \:\mathrm{9}°\:\mathrm{sin}^{\mathrm{2}} \:\mathrm{9}°\:−\mathrm{3}\right)}= \\ $$$$=\frac{\mathrm{2}\left(\mathrm{1}−\mathrm{8cos}^{\mathrm{2}} \:\mathrm{9}°\:\mathrm{sin}^{\mathrm{2}} \:\mathrm{9}°\right)}{\mathrm{cos}\:\mathrm{9}°\:\mathrm{sin}\:\mathrm{9}°\:\left(\mathrm{3}−\mathrm{16cos}^{\mathrm{2}} \:\mathrm{9}°\:\mathrm{sin}^{\mathrm{2}} \:\mathrm{9}°\right)}= \\ $$$$=\frac{\mathrm{4cos}\:\mathrm{36}°}{\mathrm{sin}\:\mathrm{54}°}=\mathrm{4} \\ $$
Commented by peter frank last updated on 07/Oct/22
$$\mathrm{thank}\:\mathrm{you} \\ $$